Autoantibodies to intracellular "rods and rings" structures in two patients with autoimmune hepatitis treated with azathioprine. (17th August 2020) - Galaski, Johanna; Koop, Anja C.; Lütgehetmann, Marc; Lohse, Ansgar W.; Weiler-Normann, Christina
Abstract: In vitro, inhibition of the synthesis of guanosine monophosphate (GMP) by various drugs such as ribavirin, acyclovir, azathioprine, and mycophenolic acid leads to the formation of subcellular structures in cultured cells. Autoantibodies targeting these cellular structures can be detected as "rods and rings" (RR) patterns by immunofluorescence. In vivo, autoantibodies to RR have been almost exclusively associated with hepatitis C virus patients treated with pegylated interferon-α and ribavirin. However, longitudinal data for other patient groups are scarce. Here, we reviewed 276 sequential immunofluorescence results from 127 patients with autoimmune hepatitis for the presence of RR patterns. Of 102 patients exposed to drugs known to induce RR in vitro, two patients under long-term azathioprine therapy were positive for this pattern. This is the first report of anti-RR in patients with autoimmune hepatitis and in patients treated with azathioprine.